2018
DOI: 10.1177/0956797617744771
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Confidence Predicts Information Seeking in Decision Making

Abstract: There is currently little direct evidence regarding the function of subjective confidence in decision making: The tight correlation between objective accuracy and subjective confidence makes it difficult to distinguish each variable's unique contribution. Here, we created conditions in a perceptual decision task that were matched in accuracy but differed in subjective evaluation of accuracy by orthogonally varying the strength versus variability of evidence. Confidence was reduced with variable (vs. weak) evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
256
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(323 citation statements)
references
References 39 publications
30
256
2
Order By: Relevance
“…We observed that proportional increases in grating and noise contrast selectively boosts confidence ratings, but not discrimination or estimation accuracy (Samaha et al, 2016(Samaha et al, , 2019. Given the importance of accurate confidence for guiding appropriate behaviors (Desender et al, 2018;Folke et al, 2017), and the role of confidence effects in theoretical accounts of conscious perception (Brown et al, 2019;Dehaene & Changeux, 2011;Lau & Rosenthal, 2011), an understanding of why confidence diverges from accuracy in the PEB is warranted.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…We observed that proportional increases in grating and noise contrast selectively boosts confidence ratings, but not discrimination or estimation accuracy (Samaha et al, 2016(Samaha et al, , 2019. Given the importance of accurate confidence for guiding appropriate behaviors (Desender et al, 2018;Folke et al, 2017), and the role of confidence effects in theoretical accounts of conscious perception (Brown et al, 2019;Dehaene & Changeux, 2011;Lau & Rosenthal, 2011), an understanding of why confidence diverges from accuracy in the PEB is warranted.…”
Section: Introductionmentioning
confidence: 80%
“…This finding suggested that a candidate function of subjective confidence is enhancing temporal continuity between perceptual inputs. Using a related confidence-accuracy dissociation paradigm, Desender et al (2018) found that reducing confidence without changing performance led participants to seek out additional perceptual information before committing to a choice. This would suggest that an additional function of subjective confidence is to inform future decisionmaking policies.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it must be appreciated that even though we observed similar activation patterns for decision and confidence, the computations that underlie these two processes may still be very different. Such differences are implied by accuracy-confidence dissociations (Lau and Passingham, 2006;Rahnev et al, 2011bRahnev et al, , 2015Vlassova et al, 2014;Song et al, 2015;Spence et al, 2015;Zylberberg et al, 2016;Samaha et al, 2016;Boldt et al, 2017;Ferrigno et al, 2017;Desender et al, 2018), neurological phenomena such as in blindsight (Weiskrantz, 1986), and studies that delivered transcranial magnetic stimulation (TMS) to the early visual cortex and found separable effects on accuracy and confidence (Rahnev et al, 2012b(Rahnev et al, , 2013Hurme et al, 2017). Moreover, a recent study provided direct evidence that sensory neural signals are indeed used in different ways in making perceptual decisions and confidence judgments (Peters et al, 2017).…”
Section: Shared Brain Circuits For Perceptual Decision Making and Conmentioning
confidence: 99%
“…Such process of selfevaluation could be supported by areas in and around TPJ that are known to be involved in processing social information (Gusnard et al, 2001;Saxe and Kanwisher, 2003). Further, confidence evaluations are used to alter one's strategy for doing the task on subsequent trials (Desender et al, 2018) and are thus linked to control processes in the frontal and cingulate regions.…”
Section: Brain Areas More Active In Confidence Judgmentsmentioning
confidence: 99%
See 1 more Smart Citation